Branding & Endorsement : Gaya Marketing Masa Kini - Olga Febriana Yohana; Huda Febriyani; Diani Anggraeni; Nurlela Nurlela (PT Naureen Digital Education, 2023)
The occurrence of public buying interest is influenced by many factors, one of which is the latest form of marketing carried out by business owners. Branding and endorsement carried out by celeb-grams through social media such as Instagram is an effort to introduce the company's products. The purpose of this study was to find out the endorsement strategy carried out by celeb-grams or influencers and what the results were from marketing through celeb-grams or influencers. The method used for this research is descriptive qualitative. This study used interview and documentation techniques. The subject of this research is the celebrity account @sandy.ss. The results of the study state that the current marketing style in building branding products such as endorsements is the right choice in the current era of globalization because endorsements are a channel for brand communication where celebrities act as spokespersons for brands and support brands with all their attributes.